Speech text of signing ceremony memorandum of agreement between Universiti Teknologi MARA and E3mel Business Academy, Egypt / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
It is with great pleasure that I welcome you to the Virtual Signing Ceremony of Memorandum of Agreement (MoA) between Universiti Teknologi MARA (UiTM) and E3Mel Business Academy, Egypt. I am thrilled to witness the start of another important partnership that would produce exceptional and beneficial outcomes for both parties.